2015
DOI: 10.1016/j.chembiol.2015.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Neocarazostatin A Reveals the Sequential Carbazole Prenylation and Hydroxylation in the Tailoring Steps

Abstract: Neocarazostatin A (NZS) is a bacterial alkaloid with promising bioactivities against free radicals, featuring a tricyclic carbazole nucleus with a prenyl moiety at C-6 of the carbazole ring. Here, we report the discovery and characterization of the biosynthetic pathway of NZS through genome mining and gene inactivation. The in vitro assays characterized two enzymes: NzsA is a P450 hydroxylase and NzsG is a new phytoene-synthase-like prenyltransferase (PTase). This is the first reported native PTase that specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 51 publications
1
55
0
Order By: Relevance
“…MA37, neocarazostatin B, a tricyclic carbazole alkaloid derived from Ltryptophan, is converted to neocarazostatin A triol via hydroxylation at C10. 129 Two genes (NozD and E) encoding putative P450s have also been identied in the genome of Norcardiopsis sp. CMB-M0232 and are proposed to be involved in the biosynthesis of nocardioazines A and B.…”
Section: Alkaloid Biosynthesis Pathwaysmentioning
confidence: 99%
“…MA37, neocarazostatin B, a tricyclic carbazole alkaloid derived from Ltryptophan, is converted to neocarazostatin A triol via hydroxylation at C10. 129 Two genes (NozD and E) encoding putative P450s have also been identied in the genome of Norcardiopsis sp. CMB-M0232 and are proposed to be involved in the biosynthesis of nocardioazines A and B.…”
Section: Alkaloid Biosynthesis Pathwaysmentioning
confidence: 99%
“…This approach has been employed to interrogate the biosynthetic sequence of such diverse compounds as glycopeptide antibiotics [44], [45], carbapenem antibiotics [46], carbazole alkaloids [47], indole alkaloids [48], pipolythiodioxopiperazines [49], meroterpenoids [50], xanthones [51], prodiginines [52], fumonisins [53], and rhizobitoxine [54]. In many of these cases, the mutational analyses and spectral analyses were validated using complementary techniques.…”
Section: Resultsmentioning
confidence: 99%
“…[7] However,t he biosynthetic machinery associated with carbazole nucleus formation through an unexpected cyclization has not yet been elucidated ( Figure S1 in the Supporting Information). [7] However,t he biosynthetic machinery associated with carbazole nucleus formation through an unexpected cyclization has not yet been elucidated ( Figure S1 in the Supporting Information).…”
mentioning
confidence: 99%
“…To locate the gene cluster of 1,weused genomic DNAto draft the genome sequence using an Illumina DNA sequencer,w hich yielded 7.6 Mb of DNAs equences divided into 136 contigs.B ya nalogy to NZS biosynthesis, [7] we hypothesized that the CQS biosynthetic gene (cqsB)c luster would include at hiamine diphosphate (ThDP)-dependent enzyme that catalyzes aC À Cc oupling reaction between indole-3-pyruvate and pyruvate,s imilar to an early step of NZS biosynthesis.Genome analysis of the S. exfoliatus 2419-SVT2 suggested that at least 11 genes predicted to encode ThDP-dependent enzymes were present. Of these genes,only one homologous gene is located in a7 .8-kb DNAr egion consisting of 8open reading frames (ORFs), showing astrong resemblance in gene organization and homology to the NZS biosynthetic gene cluster in Streptomyces sp.M A37 (Figure S2).…”
mentioning
confidence: 99%
See 1 more Smart Citation